2017
DOI: 10.4317/medoral.21965
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy and anesthetic infiltration for orofacial pain in patients with fibromyalgia: a randomized clinical trial

Abstract: BackgroundTo compare the analgesic effect of anesthetic infiltration of lidocaine 2% and low-level laser therapy (LLLT) by GaAlAs into tender points of patients with orofacial pain and fibromyalgia (FM).Material and MethodsA randomized clinical trial was performed with adults (N=66) that were allocated into two groups (1:1): Group A received LLLT irradiation by Diode Laser GaAlAs (780nm) with expositions twice a week during six weeks and Group B was treated with anesthetic infiltration of lidocaine 2% without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…Badania dowodzą, że laseroterapia jest skuteczna w poprawie jakości życia i stanu funkcjonalnego pacjentów z fibromialgią [34]. W porównaniu do zastrzyków zawierających lidokainę, efekt przeciwbólowy jest taki sam [35]. Zmniejszenie bólu, poprawa sprawności mięśni czy spadek objawów depresji to najczęstsze efekty stosowania terapii laserem niskoenergetycznym (LLLT).…”
Section: Leczenie Niefarmakologiczne Związane Z Fizjoterapiąunclassified
“…Badania dowodzą, że laseroterapia jest skuteczna w poprawie jakości życia i stanu funkcjonalnego pacjentów z fibromialgią [34]. W porównaniu do zastrzyków zawierających lidokainę, efekt przeciwbólowy jest taki sam [35]. Zmniejszenie bólu, poprawa sprawności mięśni czy spadek objawów depresji to najczęstsze efekty stosowania terapii laserem niskoenergetycznym (LLLT).…”
Section: Leczenie Niefarmakologiczne Związane Z Fizjoterapiąunclassified
“…According to American College of Rheumatology -ACR, it is a musculoskeletal chronic condition which is characterized by pain which is generalized and the body is sensitive when 11-18 points at specific areas also called tender points, are palpated during 3 months. 19 Various treatment options are available for relieving the fibromyalgia symptoms like instructions to the patient, exercises, psychotherapy, alternative medicine, pharmacologic treatment and Low Level Laser Therapy. Recent studies have shown that the low level laser therapy efficiently relieves pain in patients having fibromyalgia.…”
Section: Fibromyalgiamentioning
confidence: 99%
“…Most of the studies included in this integrative review presented positive results for pain management in the head and neck muscles (1,6,11,13,15,(17)(18)(19)(23)(24)(25)(26)(27)(28)(29)(30)(32)(33)(34)(35)(38)(39)(40)42,44,46,(50)(51)(52)(53)(54)(55)(56)(57) . For pain, there is evidence that PBM blocks the axonal transport of thin nerves, resulting in decreased mitochondrial membrane potential with a consequent decrease in the available ATP necessary for nerve function (11,62) .…”
Section: Painmentioning
confidence: 99%